Correlation Study Of Sulphur and Ash Content In Patappa Coal Area Pujananting Sub-District Barru District - Juradi, Muhammad Idris (Journal of Geology and Exploration, 2024)
Coal is an organic sedimentary rock derived from the decomposition of various plant remains which is a heterogeneous mixture of organic compounds and inorganic substances that fuse under the weight of the strata that crush it. This research is devoted to determining the correlation between ash content and sulfur content in Patappa coal area, Pujananting sub-district, Barru Regency. The purpose of this study is to determine whether there is a correlation between ash content and sulfur content in Patappa coal. The research method carried out in this research is the first preliminary stage including administration, literature study and discussion, then the data collection stage includes primary data and secondary data, the stage of data analysis and processing is to determine the correlation between ash content and sulfur content based on the analysis results. The materials used in this research include geological hammer, compass, GPS, sample bag, camera and roll meter. the sampling process carried out is by using channel sampling. The results of the analysis of this study are in sample 1, it can be seen that the value of the ash content is 18.32%, while the sulfur content has a value of 7.22%. In sample 2, the ash content value is 15.58% while the sulfur content has a value of 8.63%. So it can be concluded that the relationship between the two analyses is inversely proportional where the higher the ash content value, the lower the sulfur content value, and vice versa, the lower the ash content value, the higher the sulfur content value.